Detection criterion as the influencing factor of the database size for biometric access control systems - Фесенко, Андрей Алексеевич (Ukrainian Information Security Research Journal, 2016)
In this study for improving performance of processing the iris and decreasing database capacity, for storing iris images proposed pre-processing input images by DOG-filter or Gabor filter followed by calculation of the Hamming distance by code of the iris and its statistical parameters. Evaluation of distortion impact on the iris image of the eye, on the statistical parameters (density of probability distribution) Hamming distance. Comparisons Hamming distance between two iris images and the decision of their identity. Statistical detection criteria are chosen to reduce the database capacity, pre-processed images of the iris, and speed of identification and authentication controls and access control iris.